2014
DOI: 10.1002/cyto.b.21185
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous vitality and DNA-fragmentation measurement in spermatozoa of smokers and non-smokers

Abstract: No deleterious effect of smoking on spermatozoa was found in our study. More studies concerning potential mutagenic capacities of cigarette smoke on spermatozoa are necessary. In addition, the coupled vitality-DNA fragmentation analysis may orient Assisted Reproductive Technology teams when confronted with patients having a high percentage of DNA-fragmented living spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Previous studies reported that cigarette smoking can cause chromosomal aberration, DNA damage, and alter the DNA methylation pattern in sperms. 30,31 Several mechanisms have been hypothesized. These mechanisms were concerning the deterioration of spermatogenesis, induction of ultrastructural abnormalities, apoptosis, and abnormal epigenetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that cigarette smoking can cause chromosomal aberration, DNA damage, and alter the DNA methylation pattern in sperms. 30,31 Several mechanisms have been hypothesized. These mechanisms were concerning the deterioration of spermatogenesis, induction of ultrastructural abnormalities, apoptosis, and abnormal epigenetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA damage is partly associated with male infertility [ 17 ]. The normal reproductive processes, including sperm-egg fusion, membrane fusion, chromosome combination, and embryogenesis, can only be accomplished by sperm with intact DNA [ 18 ]. Up to now, few researchers have used DFI to examine the effect of two organisms on male infertility in China.…”
Section: Introductionmentioning
confidence: 99%
“…De Bantel et al, (2014) No significant difference was seen in coupled vitality and DNA fragmentation analysis between infertile men who were smokers and those who were nonsmokers. Belcheva, Ivanova-Kicheva, Tzvetkova, and Marinov, (2004) Overall, there is a clear negative trend in the association of smoking and sperm DNA integrity.…”
Section: Rosiakmentioning
confidence: 93%
“…De Bantel et al, (2014) No significant difference was seen in coupled vitality and DNA fragmentation analysis between infertile men who were smokers and those who were nonsmokers.…”
Section: Artmentioning
confidence: 93%